2021
DOI: 10.1177/09732586211048034
|View full text |Cite
|
Sign up to set email alerts
|

Vlogger’s Reputation: Connecting Trust and Perceived Usefulness of Vloggers’ Recommendation with Intention to Shop Online

Abstract: The study aims to determine the impact of vlogger’s reputation on viewers’ trust on vlogger’s recommendations (TVR) and perceived usefulness of vlogger’s recommendations (PUVR). Moreover, the study examines the impact of TVR and PUVR on attitude and intention to shop online. A sample of 250 responses was collected from social media users and structural equation analysis technique was employed. The findings indicate that vlogger’s reputation has a significant role in building TVR, and PUVR and TVR and PUVR sign… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 109 publications
0
1
0
Order By: Relevance
“…The study found that vlog coverage positively affected attitudes, perceived risk, and trust in vlogs, indicating that exposure to vlogs has a significant impact on viewers' trust in the information showed. These results are in line with the previous studies of (Aslam et al, 2022;Kim and Ko, 2012). Moreover, trust in vlog content was found to significantly influence trust in semi-high speed trains.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The study found that vlog coverage positively affected attitudes, perceived risk, and trust in vlogs, indicating that exposure to vlogs has a significant impact on viewers' trust in the information showed. These results are in line with the previous studies of (Aslam et al, 2022;Kim and Ko, 2012). Moreover, trust in vlog content was found to significantly influence trust in semi-high speed trains.…”
Section: Discussionsupporting
confidence: 92%
“…have shown that social media can have a positive and direct impact on trust. Vlogs, in particular, have been found to be effective in building trust (Aslam et al, 2022). However, trust transfer theory suggests that when a close affiliation exists between a trusted entity and an unknown one, trust can be transferred from the former to the latter (Chen et al, 2015;Lee et al, 2014;Wang et al, 2013;Yang et al, 2015;Yu et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Convenient student samples have been extensively used in communications research (Aslam et al, 2022; Flores-Zamora, 2022; Glaser & Reisinger, 2021; Kushin et al, 2022; Rodrigues et al, 2022). Convenience sampling helped ensure we obtained participants with similar profiles from both regions that facilitate better comparisons.…”
Section: Methodsmentioning
confidence: 99%
“…Consequently, tourists who trust YouTubers will follow their travel recommendations. Therefore, the tourism industry can use YouTubers to market and promote tourist destinations because they can be trusted to influence tourist visit intentions [63].…”
Section: -4-trustmentioning
confidence: 99%